Two Cases of Preaxial Polydactyly of the Foot: Important Implications for Plastic Surgeons. Issue 2 (February 2021) - Silverstein, Max L.; Burke, Leah W.; Laub, Donald R.
Abstract : Summary: Although polydactyly is quite common in general, preaxial polydactyly of the foot is rare (0.4 per 10, 000 patients) and specifically associated with certain congenital abnormalities and syndromes, which can include craniosynostosis, corpus callosum agenesis, and renal malformations. We present 2 recent cases of preaxial polydactyly of the foot that highlight the importance of maintaining a high level of suspicion for associated abnormalities in these patients. The first patient, who presented with supernumerary preaxial digits on both feet, pre- and postaxial polydactyly of the hands, was also macrocephalic and hyperteloric; this presentation strongly suggested a diagnosis of Greig cephalopolysyndactyly, a GLI3 -variant syndrome. The second patient, who had 2 preaxial digits on one foot, was found to also have a horseshoe kidney, a malformation that has been associated with limb defects as part of an acrorenal syndrome. These cases emphasize the importance of a thorough clinical approach to patients with preaxial polydactyly of the foot. Although many patients with this anomaly may be well known to geneticists, a child may be referred to a plastic surgeon for reconstruction of what is thought to be an isolated cosmetic or local functional issue. Plastic surgeons should be aware of the complex nature of preaxial polydactyly of the foot and potential syndromic presentation.